2022
DOI: 10.1007/s40544-021-0541-1
|View full text |Cite
|
Sign up to set email alerts
|

Reclined trend of alkyl chain of sodium dodecylbenzenesulfonate molecules induced by friction

Abstract: Surfactants tend to adsorb on the surface/interface mostly in a directional manner. The alkyl chain orientation and conformation order for molecular monolayers of sodium dodecylbenzenesulfonate (SDBS) at low concentrations are studied by using the sum frequency generation vibrational spectroscopy (SFG-VS). The molecular arrangement of the surfactants adsorbed at the solid/liquid interface is further investigated. It is found that the arrangement of the SDBS at the interface becomes relatively ordered with incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Although the surface coating of SWCNTs by surfactants is primarily for improving its dispersion stability in an aqueous environment and the separation of SWCNTs with different chirality, , the surface coating by surfactants has been reported to contribute to the enhancement of the photoluminescence of SWCNTs . Previous studies suggested that 4SDBS adsorbs on SWCNTs in two steps. The first step occurring at a low concentration is random adsorption of 4SDBS, with their hydrophobic tails parallel to the long axis of SWCNTs . At a high concentration, 4SDBS is reorganized into a more ordered adsorption with their aliphatic tails arranged perpendicular to the long axis of SWCNTs .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Although the surface coating of SWCNTs by surfactants is primarily for improving its dispersion stability in an aqueous environment and the separation of SWCNTs with different chirality, , the surface coating by surfactants has been reported to contribute to the enhancement of the photoluminescence of SWCNTs . Previous studies suggested that 4SDBS adsorbs on SWCNTs in two steps. The first step occurring at a low concentration is random adsorption of 4SDBS, with their hydrophobic tails parallel to the long axis of SWCNTs . At a high concentration, 4SDBS is reorganized into a more ordered adsorption with their aliphatic tails arranged perpendicular to the long axis of SWCNTs .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The detailed laser assembly of SFG measurements was described in Refs. [48][49][50]. The SFG setup was based on an amplified laser system (Spitfire, Spectra-Physics; 1 kHz, 100 fs) to generate pulses at 800 nm (5 mJ of energy) through a sapphire oscillator (Mai Tai, Spectra-Physics) and a high-power pump laser (Empower, Spectra-Physics).…”
Section: Sfg Measurementsmentioning
confidence: 99%